Intimate Partner Violence and Its Resolution Among African American Women - Deborah Finfgeld-Connett (SAGE Publishing, 2015)
Intimate partner violence (IPV) is a significant problem that is difficult to overcome within African American communities. Thus, the purpose of this qualitative systematic review was to synthesize isolated qualitative findings relating to IPV among African American women to make them more meaningful and generalizable. A framework of IPV among African American women resulted from this work, and key elements include the following: ubiquitous and perpetual oppression and abuse contribute to the emergence of IPV, and personal and interpersonal forms of inspiration and support are generally inadequate to prevent or resolve it. Moreover, ambivalence of others, fear, mental health problems, and negative perceptions of helping services are barriers to change. Resolution of IPV is an emergent process that is enhanced by holistic Afrocentric services. Outcomes are safety with strings attached and personal growth for mothers and children. Research hypotheses are inferred from this framework along with implications for clinical practice.